THE DIFFUSION OF VALUE EDUCATION MODEL IN EARLY CHILDHOOD THROUGH TRADITIONAL SONGS AND GAMES - Mami Hajaroh; Rukiyati Rukiyati; Joko Pamungkas (Jurnal Kependidikan, 2019)
This study was aimed at diffusing the value education model through traditional songs and games for kindergarten teachers in Yogyakarta. This model is an early childhood learning innovation for value education. Diffusion research is a study to disseminate models to teachers; therefore the research subjects were kindergarten teachers. The subject of this study in Kindergarten Schools in DIY included 15 kindergarten schools in Bantul, Sleman, Kulonprogo, Bantul and Yogyakarta city regencies involving 32 teachers. The data were gathered using focus group discussions and questionnaires. The data then analyzed using mixed descriptive qualitative and quantitative methods. This study proves that the model of value education in early childhood through traditional songs and games has five characteristics as innovations which have the advantages of relative, compatibility, complexity, can be tested and can be observed. In addition, in the process of disseminating to the teacher through five stages of diffusion, namely: knowledge, persuasion, decision, implementation, and confirmation. Teachers also tend to use traditional songs and games to inculcate religious values which are the school's peculiarities.DIFUSI MODEL PENDIDIKAN NILAI PADA ANAK USIA DINI MELALUI LAGU DAN PERMAINAN TRADISIONALPenelitian ini bertujuan untuk mendifusikan model pendidikan nilai melalui lagu dan permainan (dolanan) tradisional pada guru taman kanak-kanak ‘Aisyiyah di Daerah Istimewa Yogyakarta (DIY). Model ini merupakan inovasi pembelajaran anak usia dini untuk pendidikan nilai. Penelitian difusi merupakan penelitian untuk menyebarluaskan model kepada para guru; oleh karena itu subyek penelitian adalah guru taman kanak-kanak. Subjek penelitian ini di Sekolah Taman Kanak-kanak di DIY meliputi 15 sekolah Taman-Kanak-kanak di Kabupaten Bantul, Sleman, Kulonprogo, Bantul dan Kota Yogyakarta melibatkan 32 orang guru. Pengumpulan data menggunakan focus group discussion dan kuisioner. Analisis data secara deskriptif kualitatif dan kuantitatif. Penelitian ini membuktikan bahwa model pendidikan nilai pada anak usia dini melalui lagu dan dolanan memiliki lima karakterisik sebagai inovasi yakni memiliki keunggulan relative, kompatibilitas, kompleksitas, dapat diujicoba dan dapat diamati. Selain itu dalam proses penyebarluasan kepada guru melewati lima tahap difusi yakni: pengetahuan, persuasi, keputusan, implementasi, dan konfirmasi. Guru juga cenderung menggunakan lagu dan permainan tradisional untuk menanamkan nilai-nilai keagamaan yang merupakan kekhasan sekolah.